2017
DOI: 10.1123/apaq.2016-0017
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Children With Disabilities in Physical Education: A Systematic Review of Literature From 2009 to 2015

Abstract: This systematic review examines research published from 2009 to 2015 on inclusion of children with disabilities in physical education according to the PRISMA guidelines. We have used a stakeholder approach as a framework for organizing and discussing the results. The searches yielded 535 studies, of which 112 were included. The systematic review outlines which stakeholder perspectives received the most attention, the main themes and findings, the methodological trends that governed the research contribution, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0
14

Year Published

2017
2017
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 0 publications
5
70
0
14
Order By: Relevance
“…Unfortunately, only very limited evidence exists thus far for examining aspects of inclusion processes of students with disabilities in TPPs aimed at preparing these students to be PE teachers. Furthermore, in spite of considerable research and a number of recent systematic reviews on attitudes and perspectives of PE students and teachers toward inclusion [63][64][65][66][67][68], "there is a need to bridge the intention/ behavior gap that still exists in the research on inclusion of children with disabilities in PE" ( [68], p. 330).…”
Section: Tpps In Pementioning
confidence: 99%
“…Unfortunately, only very limited evidence exists thus far for examining aspects of inclusion processes of students with disabilities in TPPs aimed at preparing these students to be PE teachers. Furthermore, in spite of considerable research and a number of recent systematic reviews on attitudes and perspectives of PE students and teachers toward inclusion [63][64][65][66][67][68], "there is a need to bridge the intention/ behavior gap that still exists in the research on inclusion of children with disabilities in PE" ( [68], p. 330).…”
Section: Tpps In Pementioning
confidence: 99%
“…The access of these students to the practice of physical education (PE) is a fundamental right for all of them, as stated by the United Nations [1]. However, physical education teachers (PET) are often frustrated with their inability to accommodate inclusion in mixed-ability PE classrooms for reasons related to students' safety or the difficulty in designing tasks that do not negatively impact the type and severity of the disability [2]. Many PE teachers feel that their education system did not sufficiently prepare them to undertake this role [3].…”
Section: Introductionmentioning
confidence: 99%
“…Most physical education teacher education (PETE) programs only require one introductory course on adapted physical education (APE; Kwon, 2018;Piletic & Davis, 2010). Research has confirmed the correlation between strong academic preparation and general physical education teachers' level of self-confidence to include students with disabilities (Elliott, 2008;Obrusnikova, 2008;Wilhelmsen & Sorensen, 2017). Teachers possessing higher levels of selfconfidence are more willing to include students with disabilities in physical education and have positive attitudes toward inclusion (Jung, Cho, & Ambrosetti, 2011).…”
Section: Michelle Greniermentioning
confidence: 95%